Statement Showing the Progress of Development Schemes Under State Sixth Five-Year Plan for 1980-85 - Planning Commission (Planning Commission, 1974)
Abstract statement shown the actual expenditure during 1978-79 and 1979-80 in of State Annual Plan Scheme as well as estimated provision during 1980-81 and 1981-82 in respect of State Sixth Five-Year Plan Schemes, 1980-85 (arranged according to Heads of Accounts) Abstract statement Showing the actual expenditure during 1978-80 in respect of State Annual Plan Scheme as well as estimated provision during 1980-81 and 1981-82 in respect of State Sixth Five-Year Plan Schemes, 1980-85 (arranged according to the Heads of Development) Abstract statement showing the actual expenditure during 1978-80 in respect of State Annual Plan Schemes as well as estimated provision during 1980-81 and 1981-82 in respect of State Sixth Five-Year Plan Schemes 1980-85 (arranged according to the Department wise Allocations) Abstract statement showing the actual expenditure as well as estimated provision during 1978-79 to 1981-82 in respect of provision programme for Minimum included under the State Plan.
Finance Department, Government of West Bengal